Penilaian keperluan dalam pembangunan komuniti - Haris Abd. Wahab; Abd. Hadi Zakaria (Kuala Lumpur : Penerbit Universiti Malaya, 2012)
Needs assessment in community development program in Malaysia.
Includes bibliographical references (p. [261]-297) and index
Keywords: Community development -- Malaysia; Needs assessment -- Malaysia